2018
DOI: 10.4103/pm.pm_152_17
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Brassica oleracea Var. capitata L. (Cabbage) methanol extract in mice with contact dermatitis

Abstract: Background:Cabbage, Brassica oleracea var. capitata L., is one of the most common vegetables in the world. Because of its high levels of flavonoids and anthocyanins, cabbage has long been used as a herbal medicine. The antioxidant and anti-inflammatory properties of cabbage were also recently been reported.Objective:This study was designed to investigate the anti-inflammatory effects of cabbage in mice with contact dermatitis (CD).Materials and Methods:We investigated the effects of methanol extract of B. oler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Although there have not been many studies investigating the biological functions of plant-derived nanovesicles, a number of studies have reported the anti-inflammatory activities of components extracted from plants using organic solvents [ [44] , [45] , [46] ]. To investigate the anti-inflammatory activities of Cabex and Rabex, RAW264.7 cells were supplemented with 0, 1 × 10 8 , 1 × 10 9 , 1 × 10 10 , and 1 × 10 11 particles mL −1 of nanovesicles and treated with LPS to induce inflammation [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although there have not been many studies investigating the biological functions of plant-derived nanovesicles, a number of studies have reported the anti-inflammatory activities of components extracted from plants using organic solvents [ [44] , [45] , [46] ]. To investigate the anti-inflammatory activities of Cabex and Rabex, RAW264.7 cells were supplemented with 0, 1 × 10 8 , 1 × 10 9 , 1 × 10 10 , and 1 × 10 11 particles mL −1 of nanovesicles and treated with LPS to induce inflammation [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The garden cabbage (Brassica oleracea L.) is widely used worldwide as a vegetable crop, traditional medicine has used it in the treatment of various diseases, including the gastrointestinal tract. Scientific publications in recent years have demonstrated the presence of cabbage pharmacological properties caused by the complex of biologically active compounds in its composition, which was the justification an experimental study of the dry extract produced from cabbage garden [8][9][10].…”
Section: Planning (Methodology) Of Researchmentioning
confidence: 99%
“…23 Apesar de não ter sido encontrada, na literatura consultada, atividade contra inflamações uterinas, há indícios de atividade anti-inflamatória em diferentes variedades de Brassica. 24 A goiaba pertence ao gênero Psidium e é uma planta alimentícia muito comum no Nordeste brasileiro. A utilização contra diarreia é muito citada na literatura provavelmente devido ao conteúdo em taninos que possuem atividades antimicrobianas e adstringentes.…”
Section: Resulatos E Discussãounclassified